2018
DOI: 10.48550/arxiv.1812.10339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstruction of $F(T)$ gravity in homogeneous backgrounds

Abstract: A technique for the reconstruction of the potential for a scalar field in cosmological models based on induced gravity has recently been developed by Alexander Y. Kamenshchik, Alessandro Tronconi, and Giovanni Venturi [73]. In this paper, this extended reconstruction method is utilized to investigate the nature of the scalar potentials of the most extended action of F (T ) -gravity context. First, a general formalism is formulated and then it is utilized for considering some well-known special cases including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…It has been demonstrated in ref. [80] that according to recent observational data, m is very close to 1. Utilizing this well-known reasonable condition, a = b m , the expansion scalar (21) takes the form…”
Section: The Model and Field Equationssupporting
confidence: 51%
See 1 more Smart Citation
“…It has been demonstrated in ref. [80] that according to recent observational data, m is very close to 1. Utilizing this well-known reasonable condition, a = b m , the expansion scalar (21) takes the form…”
Section: The Model and Field Equationssupporting
confidence: 51%
“…Based on the recent observational data, in ref. [80], it has been demonstrated that m is very close to one 4 . The case m = 1 is FRW.…”
Section: Discussionmentioning
confidence: 94%
“…Note that according to (30), the rate of σ and Θ would be equal since ( σ/σ) = ( Θ/Θ) . Pursuant to observational data, it has been demonstrated in [37,42] that…”
Section: Reconstruction Of F (R)-gravitymentioning
confidence: 99%
“…Cosmological models are investigated via several powerful tools: exact solutions, phase space [25,26], B-function method [27], Noether symmetry approach [28][29][30][31], Beyond Noether symmetry approach (B.N.S.) [32], Noether symmetry approach using CSSS-trick [33], Reconstruction methods [34][35][36][37][38], etc. Recently, a new strategy to the reconstruction of f (R) -gravity models using Raychaudhuri equation has been proposed by Choudhury et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…This further provides anisotropic relationship between the scale factors. Tajahmad [75] has considered the similar relation to reconstructed the F (T ) gravity. Most recent, Tajahmad [76] has shown that late time accelerated expansion arisen from gauge fields in an anisotropic background.…”
Section: Basic Formalism and Dynamical Parametersmentioning
confidence: 99%